Strategic modeling of enterprise business processes based on principles of organizing large-scale sporting events - Volkov, Pavlo (Актуальні питання економічних наук, 2026)
The increasing complexity of economic management and the growing interdependence of organizational functions necessitate the development of advanced managerial solutions to coordinate resources, time constraints, and multiple stakeholders. In this context, practical experience in organizing large-scale event-based projects is particularly relevant, as such activities are characterized by strict regulation, high concentration of responsibility, and the integration of heterogeneous operational functions within a unified management framework. The purpose of this study is to substantiate the applicability of managerial principles used in the planning and implementation of large-scale sporting events to the improvement of enterprise business process organization and long-term managerial coherence. Methods. The research is based on systems analysis, functional and structural generalization, comparative assessment, and elements of the process-oriented management approach. The theoretical foundation includes concepts of strategic management, the economic organization of enterprises, and best practices for managing complex projects under elevated risk and limited timeframes. Results. The study identifies key managerial principles inherent in large-scale sporting event organization, including centralized coordination, modular operational structuring, phased performance monitoring, and formalized interaction between responsible units. The feasibility of integrating these principles into enterprise management systems is substantiated in order to enhance internal coordination, reduce operational inefficiencies, and increase organizational adaptability to environmental changes. A conceptual logic for managerial decision-making focused on result orientation and temporal discipline is proposed. Conclusions. It is proven that making management decisions based on the principles of organizing large-scale sporting events improves the manageability of economic processes, optimizes resource provision, and strengthens the strategic stability of enterprises. The results obtained have practical value for managers and specialists responsible for developing and implementing economic management decisions.